PATHOPHYSIOLOGY AND PRINCIPLES OF THERAPY OF A NEUROGENIC HYPERACTIVE URINARY BLADDER IN PATIENTS AFTER CEREBROVASCULAR ACCIDENT - P. G. Shchvartz; S. V. Popov; A. V. Bershadskiy (Исследования и практика в медицине)
Neurogenic hyperactiv e bladder in different clinical variations is a characteristic com plication of restorativ e and residual periods of ischemic stroke and an important diagnostic criterion in vascular dementia. Mechanisms of formation of individual symptoms included in this syndrome is due to ischemic damage to cortical, subcortical and brainstem (the nucleus of Barrington) centres of urination and associative areas of the brain, and the functional dissociation of these structures due to demyelination of the Central conductors of the afferent and efferent impulses. As a result of deficit of cerebral effects (such as brake and activating), is a violation of the implementation of the reflexes of urination (including carrying out continence), ongoing spinal (sympathetic, parasympathetic and somatic). The article presents a new concept of formation of the syndrome of hyperactive bladder on the basis of violations of the implementation of the 4 reflexes of urination, which provides the normal retention of urine and are responsible for the accumulation function of the bladder. First we analyzed the main point of application of drugs of anticholinergic and sympathomimetic actions in the reflexes of urination and mechanisms of restoration of function of the lower urinary tract in patients with acute and chronic v ascular diseases of the brain.